2021
DOI: 10.3390/antibiotics10101206
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance of Listeria monocytogenes Strains Isolated from Humans, Animals, and Food Products in Russia in 1950–1980, 2000–2005, and 2018–2021

Abstract: Susceptibility of 117 L. monocytogenes strains isolated during three time periods (1950–1980; 2000–2005, and 2018–2021) to 23 antibiotics was tested by the disk diffusion method. All strains were sensitive to aminoglycosides (gentamicin, kanamycin, neomycin, streptomycin), glycopeptides (vancomycin and teicoplanin), clarithromycin, levofloxacin, amoxicillin/clavulanic acid, and trimethoprim/sulfamethoxazole. Resistance to clindamycin was observed in 35.5% of strains. Resistance to carbapenems, imipenem and mer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 41 publications
(59 reference statements)
3
15
0
3
Order By: Relevance
“…In another study [ 34 ], all the isolates of the Listeria species were observed to be resistant against penicillin and imipenem (100%), followed by trimethoprim (75%). Another study [ 35 ] showed resistance to carbapenems, imipenem, and meropenem in 4% and 5% of strains collected from humans, animals, and food products in Russia, respectively. On other hand, 100% resistance to imipenem was recorded in [ 34 ]; however, gentamicin and meropenem appeared to be the most effective antibiotics, as all Listeria species isolates were susceptible to them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study [ 34 ], all the isolates of the Listeria species were observed to be resistant against penicillin and imipenem (100%), followed by trimethoprim (75%). Another study [ 35 ] showed resistance to carbapenems, imipenem, and meropenem in 4% and 5% of strains collected from humans, animals, and food products in Russia, respectively. On other hand, 100% resistance to imipenem was recorded in [ 34 ]; however, gentamicin and meropenem appeared to be the most effective antibiotics, as all Listeria species isolates were susceptible to them.…”
Section: Discussionmentioning
confidence: 99%
“…Vancomycin susceptibility (97.9%) was the highest among all tested antibiotics, as recorded in [ 2 ], which found that all L. monocytogenes strains (100) were susceptible to vancomycin. In contrast, all L. monocytogenes strains were resistant to vancomycin in [ 35 ]. Our findings reveal that 100% of the examined L. monocytogenes had MAR ranging from 0.33 to 0.88, which matches the result of Elsayed et al [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…№2 АНТИБИОТИКОРЕЗИСТЕНТНОСТЬ ным значением между устойчивыми и чувствительными штаммами L. mono cytogenes [23]; для 8 штаммов размер зоны подавления роста составил 17 мм (Рисунок 4). Для более наглядного представления результатов мы срав нили размеры зон подавления роста к ампициллину и бензилпенициллину у исследованных штаммов и у штам мов, выделенных на территории России в 1950-1980 гг., чувствительность которых была определена ранее с ис пользованием дисков того же производителя (Рисунок 4) [14]. Аналогичный сдвиг в размере зон подавления ро ста наблюдали и в устойчивости к бензилпенициллину.…”
Section: определение профиля антибиотикорезистентностиunclassified
“…Том 24 . №2 АНТИБИОТИКОРЕЗИСТЕНТНОСТЬ числе множественной, устойчивости к антибиотикам, особенно среди клинических изолятов и изолятов, выде ленных из окружающей среды [14][15][16].…”
Section: Introductionunclassified
“…Antibiotic treatment options for L. monocytogenes infections include cell wall synthesis disruptors ampicillin and vancomycin, folic acid synthesis inhibitors sulfamethoxazole and trimethoprim, and protein synthesis inhibitors, such as gentamicin and azithromycin [33]. L. monocytogenes strains reported in recent years are often resistant to clindamycin, with the resistant fraction ranging from 29% to 76%, depending on the collection [34][35][36][37], thus excluding clindamycin as a viable option for treatment of L. monocytogenes infections. Importantly, just as E. faecalis encodes the ABCF ATPase LsaA, L. monocytogenes encodes the ARE ABCF PLSA resistance factor VgaL/Lmo0919 in its core genome [38].…”
Section: Introductionmentioning
confidence: 99%